Job Crafting on Job Satisfaction: the mediating role of Work Engagement - Yogantara, Bima Olga; Zona, Mega Asri (Human Resource Management Studies, 2023)
This study plans to break down the effect of job crafting on job satisfaction at the HR and General department of PT. SP Manufacturing with work engagement as an interceding variable. The sort of exploration utilized is quantitative examination. This exploration is a causal examination. The populace in this study were each of the 63 representatives of the HR and General department of PT. SP Manufacturing Padang City. The inspecting strategy utilizes soaked testing where all individuals from the populace are utilized as tests. Gathering information utilizing a poll with a Likert scale. The strategy for examination utilizing Partial Least Square utilizing the Smart PLS program. The after effects of information handling in this study demonstrate that: (1) job crafting has a positive and significant effect on job satisfaction at the HR and General department of PT. SP Manufacturing Padang City (2) job crafting has a positive and significant effect on work engagement at the HR and General department of PT. SP Manufacturing Padang City (3) work engagement has an effect positive and significant effect on job satisfaction at the HR and General department of PT. SP Manufacturing Padang City (4) job crafting has a positive and significant effect on job satisfaction through work engagement at the HR and General department of PT. SP Manufacturing Padang City.